2003
DOI: 10.1126/science.1080115
|View full text |Cite
|
Sign up to set email alerts
|

Spread of HTLV-I Between Lymphocytes by Virus-Induced Polarization of the Cytoskeleton

Abstract: Cell contact is required for efficient transmission of human T cell leukemia virus- type 1 (HTLV-I) between cells and between individuals, because naturally infected lymphocytes produce virtually no cell-free infectious HTLV-I particles. However, the mechanism of cell-to-cell spread of HTLV-I is not understood. We show here that cell contact rapidly induces polarization of the cytoskeleton of the infected cell to the cell-cell junction. HTLV-I core (Gag protein) complexes and the HTLV-I genome accumulate at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
634
1
15

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(658 citation statements)
references
References 28 publications
8
634
1
15
Order By: Relevance
“…Tax appears to be localized partially in the cis-Golgi adjacent to the microtubule organizing center in naturally infected T lymphocytes from HTLV-1-associated myelopathy/tropical spastic paraparesis patients (29). It has been suggested that Tax promotes microtubule polymerization, in cooperation with ICAM-1 engagement, leading to the formation of the virological synapse that enables cell-to-cell spread of HTLV-1 (29,35). Based on our results, one possibility is that Tax may recruit IKK to the vicinity of the Golgi/micro-tubule organizing center to facilitate IKK-mediated phosphorylation of targets necessary for microtubule polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Tax appears to be localized partially in the cis-Golgi adjacent to the microtubule organizing center in naturally infected T lymphocytes from HTLV-1-associated myelopathy/tropical spastic paraparesis patients (29). It has been suggested that Tax promotes microtubule polymerization, in cooperation with ICAM-1 engagement, leading to the formation of the virological synapse that enables cell-to-cell spread of HTLV-1 (29,35). Based on our results, one possibility is that Tax may recruit IKK to the vicinity of the Golgi/micro-tubule organizing center to facilitate IKK-mediated phosphorylation of targets necessary for microtubule polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…As 1 example, with our model that adjusted for the frequencies of the other class II haplotypes, In contrast to individual types, we did have good statistical power to assess whether more common types were associated with disease risk. Given that HTLV-I is tightly cell associated and viral protein is expressed on the cell surface, 11 HLA can be postulated to play an important role in recognizing such cells as foreign and mounting an effective immune response against them. Indeed, Biggar et al noted that concordance in HLA class I alleles between a mother and her infant was a strong risk factor for transmission by breast feeding.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, HIV viral load is significantly lower with rare HLA class I supertypes and perhaps alleles. 9,10 HTLV-I is transmitted primarily by cell-to-cell contact, 11 and transmission from mother to infant is directly related to burden of infection in the mother (proviral load) 12 and is significantly increased for mothers and infants who are highly HLA concordant. 13 In the present study, we examined HLA gene polymorphisms of 305 Jamaican subjects with HTLV-I infection, postulating that people with higher prevalence HLA types may develop an immune response against a narrower range of cell-associated viral or neoplastic antigens and consequently may be at higher risk of ATL or HAM/TSP.…”
mentioning
confidence: 99%
“…In the case of the human immunodeficiency virus (HIV) and the human T cell lymphoma virus these cell-cell contacts share features with immunological synapses and have been designated infectious or virological synapses (13,14,19,29,41). Using the murine leukemia virus (MLV) as a model system, we demonstrated that the interaction between the viral Env glycoprotein (Env), expressed on the infected cell and the viral receptor, expressed on the uninfected target cell, leads to the establishment of cell-cell contacts (32,45).…”
mentioning
confidence: 99%